A surface treatment process for reducing the gloss of synthetic mica to increase its skin-like smoothness in situ by a single treatment agent

CN122894237APending Publication Date: 2026-10-13NINGBO SHANGYOU BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611403981.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

第一类是单一硬脂酸直接包覆工艺,该方法通过硬脂酸在云母表面形成包覆层,但硬脂酸单一包覆层与云母基底之间的附着力较弱,在彩妆产品高速搅拌灌装、粉体压片成型等工艺过程中,包覆层极易发生脱落和剥离,导致改性效果失效

Benefits of technology

第一,附着力显著增强:通过湿法原位生成工艺,在云母表面直接生成脂肪酸镁盐包覆层,而非传统工艺中的物理吸附方式,使包覆层与云母基底形成化学键合,解决了现有技术中硬脂酸单一包覆层在高速搅拌灌装、粉体压片成型等工艺过程中易脱落剥离的技术问题,原位生成的包覆层在500次高速搅拌测试后保留率仍达95%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894237A_ABST
    Figure CN122894237A_ABST
Patent Text Reader

Abstract

The application discloses a surface treatment process of a single treatment agent for reducing gloss of synthetic mica and increasing skin-friendly smoothness of the synthetic mica by in-situ generation, and the process comprises the following steps: after pulp preparation of synthetic fluorophlogopite, a fatty acid treatment agent is added, and then in-situ reaction is carried out with a magnesium hydroxide suspension liquid at 60-80 DEG C to generate a fatty acid magnesium salt coating layer; after washing and heat treatment, the mica sheet structure is destroyed by ultrafine grinding to form a micro-rough surface. By means of the wet in-situ generation technology, the fatty acid magnesium salt coating layer is chemically bonded with the mica substrate, and the adhesion is significantly enhanced; meanwhile, the ultrafine grinding is used to generate irregular morphology on the mica surface, effectively scatter incident light, and realize the matt and foggy surface effect. The modified mica powder prepared by the process has the advantages of light and thin skin feeling, good dispersion stability, good compatibility with oil, and is suitable for high-end cosmetic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cosmetic powder surface modification technology, and in particular to a surface treatment process using a single treatment agent in situ to reduce the gloss of synthetic mica and increase its skin-adhesive and smooth feel. Background Technology

[0002] High-purity flake-shaped synthetic fluorophlogopite is an important dual-purpose powder raw material for pearlescent base and skin-feel filler in the current color cosmetics industry. It has many core advantages, such as high flake regularity, pure powder whiteness, excellent acid and alkali resistance, non-yellowing during high-temperature color cosmetic processing, uniform and stable original luster, and compliant and controllable heavy metal residues. At the same time, the cost can be controlled by large-scale procurement, which can well meet the needs of mass production in the beauty industry.

[0003] However, to meet the formulation requirements and final makeup effects of different color cosmetic products, synthetic fluorophlogopite powder usually requires surface modification treatment. Currently, the mainstream modification methods in the industry mainly include the following three types of processes. The first type is the single stearic acid direct coating process. This method forms a coating layer on the mica surface using stearic acid. However, the adhesion between the single stearic acid coating layer and the mica substrate is weak. During high-speed mixing and filling, powder pressing, and other processes in color cosmetic products, the coating layer is prone to detachment and peeling, leading to the failure of the modification effect. The second type is the silane coupling agent physical adhesion coating process. This process uses silane coupling agents to physically attach the modified components to the mica surface. However, the powder modified with silane coupling agents has a relatively thick feel and cannot meet the market demand for the current mainstream matte, light luxury color cosmetic formulation system. The third type is the single magnesium salt non-saponification composite coating process. This method directly uses purchased finished magnesium myristate powder to mix and coat mica. However, since magnesium myristate only binds to the surface of mica through physical adsorption, the binding force is weak, which easily leads to powder agglomeration. As a result, the modified mica has poor dispersion stability in the organic system, affecting the quality and performance of the final color cosmetic product.

[0004] Therefore, how to develop a process technology that can effectively reduce the gloss of synthetic mica, increase its skin-friendly and smooth feel, and achieve surface treatment of a single treatment agent through in-situ generation has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0005] The purpose of this invention is to provide a surface treatment process using a single treatment agent in situ to reduce the gloss of synthetic mica and increase its skin-friendly and smooth feel, thereby solving the problems mentioned in the background art.

[0006] This invention is achieved through a surface treatment process using a single-agent in-situ generation method to reduce the gloss of synthetic mica and increase its skin-friendly smoothness, comprising the following steps: S1, Slurry preparation: Add synthetic fluorophlogopite to deionized water, slurry until the solid content is 50%, control the temperature at 60-80℃, stir at 200-400 rpm for 10 minutes to fully disperse the mica powder and form a uniform slurry. S2, Addition of organic acid treatment agent: Add 0-5% of the mass of synthetic fluorophlogopite to the slurry obtained in step S1 as a fatty acid or amino acid treatment agent, and continue stirring for 20 minutes at a temperature of 60-80℃ until the treatment agent is completely dissolved and uniformly dispersed in the slurry system. S3, Preparation of magnesium hydroxide suspension: Dissolve magnesium hydroxide in deionized water, ultrasonically disperse for 30 minutes to prepare a 10% suspension, adjust the pH to 9-10 using an alkaline regulator, and stir at 150-200 rpm for 10 minutes to obtain a uniform magnesium hydroxide suspension. S4, In-situ reaction: Add 0-5% of the magnesium hydroxide suspension prepared in step S3 to the slurry of synthesized fluorophlogopite in step S2, and continue to stir at 250-350 rpm for 30 minutes while maintaining a temperature of 60-80℃, so that the fatty acid or amino acid treatment agent can fully contact and react with magnesium hydroxide. Then, the temperature is increased to 90℃ at a rate of 2℃ / min, and the reaction is maintained at 90℃ for 10 hours to complete the reaction process of in-situ generation of fatty acid magnesium salt coating layer. S5, Drying and Washing: The material after the reaction in step S4 is dried in a vacuum drying oven at a temperature of 80-100℃ for 4-6 hours to obtain a cake-like material. The cake-like material is then transferred to a washing tank and deionized water is added for repeated washing. The washing temperature is controlled at 60-70℃ and the washing continues until the pH of the filtrate is 7-9, thus completing the removal of impurities. S6, Heat treatment: Place the cake material washed in step S5 into a heat treatment furnace, heat it to 100°C at a heating rate of 3°C / min, and keep it at 100°C for 6 hours to complete the heat stabilization treatment, so that the fatty acid magnesium salt coating layer forms a stable chemical bond with the mica substrate. S7, Ultrafine Grinding: The cake-shaped material after heat treatment in step S6 is processed by ultrafine grinding. The speed of the ultrafine grinder is set to 8000-12000 rpm, the grinding time is 15-30 minutes, and after grinding, it is passed through a 200-mesh sieve to obtain the finished product, matte synthetic fluorophlogopite after composite modification.

[0007] Furthermore, the particle size range of the synthesized fluorophlogopite in step S1 is 10-100μm, preferably 20-60μm, with high integrity of its sheet-like structure, whiteness not less than 95%, silica content ≤0.1%, and heavy metal residues meeting cosmetic-grade safety standards.

[0008] Furthermore, the fatty acid or amino acid treatment agent mentioned in step S2 is selected from one or more of myristic acid, lauric acid, palmitic acid, and stearic acid, and is a combination with an amino acid derivative. The modification effect is best when the amount of treatment agent added is 1-3% of the mass of the synthesized fluorophlogopite.

[0009] Furthermore, in the preparation process of the magnesium hydroxide suspension in step S3, ultrasonic dispersion is performed using an ultrasonic cleaner with a frequency of 20-40 kHz for 30 minutes to ensure that the magnesium hydroxide particles are fully dispersed and have a uniform particle size distribution.

[0010] Furthermore, during the in-situ reaction in step S4, the fatty acid or amino acid treatment agent undergoes a dual action of saponification and adsorption with magnesium hydroxide, generating a fatty acid magnesium salt coating layer in situ on the mica surface. This coating layer forms a chemical bond with the mica substrate, rather than physical adsorption, which significantly improves the adhesion and durability of the coating layer.

[0011] Specifically, the purpose of controlling the heating rate and holding time in step S4 is to ensure that the fatty acid magnesium salt coating layer can completely cover the mica surface and form a uniform and dense coating structure, while enabling the coating layer and mica to complete chemical bonding and form a stable interface structure.

[0012] Furthermore, the ultrafine pulverization process described in step S7 uses high-speed mechanical impact and shearing to destroy the large sheet-like structure of mica, causing microscopic roughening of the mica surface and forming an irregular geometric morphology. This roughened surface can effectively scatter incident light, significantly reduce surface gloss, and achieve a matte finish.

[0013] Among them, the parameter control of the ultra-fine pulverization process in step S7 is particularly critical. When the rotation speed is below 8000 rpm, the mica sheet structure cannot be effectively destroyed, and the matte effect is not obvious. When the rotation speed is above 12000 rpm, the powder will be too fine, affecting its dispersion performance and skin feel in the makeup formula.

[0014] Furthermore, the purpose of controlling the pH value at the washing endpoint in step S5 within the range of 7-9 is to remove unreacted magnesium hydroxide and byproducts from the reaction system, ensuring that the pH value of the final product is weakly alkaline to neutral, which meets the safety requirements of cosmetic raw materials.

[0015] Furthermore, during the heat treatment process in step S6, an excessively rapid heating rate can cause thermal stress in the coating layer, resulting in cracks. Insufficient holding time will prevent the fatty acid magnesium salt coating layer from fully curing, affecting its bonding strength with the mica substrate.

[0016] The beneficial effects of this invention are as follows: First, the adhesion is significantly enhanced: through a wet in-situ generation process, a fatty acid magnesium salt coating layer is directly generated on the mica surface, rather than the physical adsorption method in the traditional process. This allows the coating layer to form a chemical bond with the mica substrate, solving the technical problem that the stearic acid single coating layer is easy to fall off and peel off during high-speed stirring and filling, powder tableting and molding processes in the existing technology. The in-situ generated coating layer still has a retention rate of over 95% after 500 high-speed stirring tests.

[0017] Secondly, it has an excellent matte finish: it uses a special ultra-micro pulverization process to destroy the regular large sheet structure of mica, making its surface micro-roughened and irregular geometric morphology. This roughened surface can effectively scatter incident light and significantly reduce the surface gloss, which can be reduced to below 5GU, forming a delicate matte texture, which is suitable for the needs of high-end matte makeup products.

[0018] Third, it has good dispersion stability: the in-situ generated fatty acid magnesium salt coating layer uniformly and densely covers the surface of mica, effectively solving the agglomeration problem caused by direct mixing of purchased powders, and significantly improving the dispersion stability of modified mica in organic systems. After 30 days of accelerated storage at 60℃ in lipstick formulation, no flocculation or precipitation was observed, and the dispersion stability was improved by more than 3 times.

[0019] Fourth, it has a light and smooth feel: the magnesium salt coating of fatty acids has a light texture and good compatibility with oils. The coating thickness is only 50-100nm, which avoids the heavy and sticky feeling brought about by the modification of silane coupling agents, and gives the mica powder a skin-friendly and smooth feel, improving the skin feel score by more than 40%.

[0020] Fifth, the process is environmentally friendly and efficient: the entire process is a wet process, with no dust pollution problems, the process flow is simple and controllable, the reaction conditions are mild, it is easy to scale up industrial production, and the production cost is reduced by more than 20% compared with existing technologies. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of a surface treatment process using a single treatment agent in situ to reduce the gloss of synthetic mica and increase its skin-friendly and smooth feel. Figure 2 This is a product microscopic comparison image of a surface treatment process using a single treatment agent in situ to reduce the gloss of synthetic mica and increase its skin-friendly and smooth feel. Under the microscope, the MM treatment is thinner and more transparent, with a significant reduction in agglomeration. Figure 3 This is a particle size analysis table of a surface treatment process using a single treatment agent to reduce the gloss of synthetic mica and increase its skin-friendly and smooth feel. The particle size distribution of MM-treated powder is close to that of untreated powder, while the particle size distribution of AS-treated powder is significantly larger than that of untreated powder. Figure 4This is a product comparison table of surface treatment processes using a single treatment agent in situ to reduce the gloss of synthetic mica and increase its skin-friendly and smooth feel. Detailed Implementation

[0022] The following is combined Figure 1 The process flow diagram shown illustrates in detail the in-situ matte surface treatment process for synthesized fluorinated phlogopite of the present invention. Figure 1 The entire process from raw material addition to finished product packaging is fully demonstrated, including key steps such as slurry preparation, addition of organic acid treatment agent, preparation of magnesium hydroxide suspension, in-situ reaction, drying and washing, heat treatment, and ultrafine grinding. The key process parameters marked in the figure are temperature control range of 60℃ to 100℃, pH adjustment range of 9 to 10, and pH range of washing endpoint of 7 to 9. The specific values ​​of these parameters will be explained in detail in conjunction with the following examples.

[0023] This invention addresses the shortcomings of existing synthetic fluorophlogopite surface modification processes, such as weak coating adhesion, a heavy feel, and poor dispersion stability due to easy agglomeration. It provides a wet in-situ method for directly forming a fatty acid magnesium salt coating layer on the mica surface. The core innovation of this process lies in utilizing the in-situ saponification reaction of fatty acids or amino acid-based treatment agents with magnesium hydroxide in a mica slurry system to achieve chemical bonding between the coating layer and the mica substrate, rather than traditional physical adsorption. This significantly improves the adhesion and durability of the coating layer. Simultaneously, a special ultra-fine grinding process is used to micro-roughen the surface of the coated mica, creating an irregular geometric morphology that effectively scatters incident light, achieving an excellent matte finish.

[0024] In the specific implementation process, the slurry preparation work in step S1 is carried out first. Synthetic fluorophlogopite meeting cosmetic-grade safety standards is added to deionized water and slurried until the solid content is 50%. In a preferred embodiment of the invention, the particle size range of the synthetic fluorophlogopite is controlled between 20 and 60 μm. Within this particle size range, the mica's flake structure has high integrity, whiteness not less than 95%, silica content ≤0.1%, and heavy metal residues meet cosmetic-grade safety standards. The slurry temperature is controlled at 60 to 80°C, and the mixture is stirred at 200 to 400 rpm for 10 minutes to fully disperse the mica powder and form a uniform slurry. In this step, the selection of the stirring speed is crucial. When the speed is below 200 rpm, the mica powder is difficult to disperse fully in water, easily forming local agglomerates and affecting the subsequent reaction effect; when the speed is above 400 rpm, too many bubbles may be generated, interfering with the stability of the reaction system.

[0025] After the slurry preparation is completed, the process proceeds to step S2, which involves adding an organic acid treatment agent. 0 to 5% (by weight of synthetic fluorophlogopite) of a fatty acid or amino acid treatment agent is added to the slurry obtained in step S1. In a preferred embodiment of this invention, the fatty acid or amino acid treatment agent is selected from one or more of myristic acid, lauric acid, palmitic acid, and stearic acid, combined with an amino acid derivative. The optimal modification effect is achieved when the amount of treatment agent added is 1 to 3% (by weight of synthetic fluorophlogopite). The mixture is stirred for 20 minutes at a temperature of 60 to 80°C to ensure complete dissolution and uniform dispersion of the treatment agent in the slurry system. Within this temperature range, the fatty acid treatment agent maintains good solubility while preventing excessively high temperatures that could lead to fatty acid oxidation and decomposition. The choice of treatment agent directly affects the performance of the final coating layer. Myristic acid, due to its moderate carbon chain length, exhibits good skin feel and dispersion properties when forming salts with magnesium ions, making it a preferred option in this invention.

[0026] The preparation of the magnesium hydroxide suspension in step S3 is then carried out. Magnesium hydroxide is dissolved in deionized water and ultrasonically dispersed for 30 minutes using an ultrasonic cleaner with a frequency of 20 to 40 kHz to prepare a 10% suspension. The pH is adjusted to 9 to 10 using an alkaline adjuster, and the suspension is stirred at 150 to 200 rpm for 10 minutes to obtain a homogeneous magnesium hydroxide suspension. Ultrasonic dispersion aims to ensure that the magnesium hydroxide particles are fully dispersed and have a uniform particle size distribution, avoiding particle agglomeration that could affect the reaction. The alkaline conditions of a pH of 9 to 10 are beneficial for the subsequent saponification reaction and also maintain the stability of the magnesium hydroxide suspension, preventing particle sedimentation.

[0027] After the preparation of the magnesium hydroxide suspension is completed, the in-situ reaction stage of step S4 is entered. 0 to 5% (by mass of synthetic fluorophlogopite) of the magnesium hydroxide suspension prepared in step S3 is added to the slurry from step S2. The mixture is stirred at 250 to 350 rpm for 30 minutes while maintaining a temperature of 60 to 80°C, ensuring sufficient contact and reaction between the fatty acid or amino acid treatment agent and the magnesium hydroxide. During this stage, the fatty acid or amino acid treatment agent undergoes a saponification reaction with the magnesium hydroxide, generating magnesium fatty acid salts. This saponification reaction is the core chemical process of this invention, and its reaction mechanism is as follows: fatty acids react with magnesium hydroxide under alkaline conditions to generate insoluble magnesium fatty acid salt precipitates. These precipitates are deposited in situ on the mica surface, forming a uniform coating layer. Subsequently, the temperature is programmed to rise to 90°C at a rate of 2°C / min, and the reaction is maintained at 90°C for 10 hours to complete the in-situ formation of the magnesium fatty acid salt coating layer. The purpose of controlling the heating rate is to ensure that the magnesium fatty acid salt coating layer can be slowly and uniformly deposited on the mica surface, forming a dense coating structure. A 10-hour heat treatment ensures the reaction proceeds completely, allowing a stable chemical bond to form between the magnesium fatty acid salt coating layer and the mica substrate.

[0028] During the in-situ reaction, fatty acid or amino acid treatment agents undergo a dual process of saponification and adsorption with magnesium hydroxide, generating a fatty acid magnesium salt coating layer on the mica surface. This coating layer forms a chemical bond with the mica substrate, rather than physical adsorption. This is the fundamental difference between this invention and existing technologies such as stearic acid-only coating, silane coupling agent physical adhesion coating, and single magnesium salt non-saponification composite coating. The formation of chemical bonds significantly improves the adhesion and durability of the coating layer, solving the technical problem of easy peeling and detachment of the coating layer during high-speed stirring filling, powder tableting, and other processes in existing technologies.

[0029] After the in-situ reaction is completed, the process proceeds to step S5, the drying and washing stage. The material from step S4 is dried in a vacuum drying oven at 80-100°C for 4-6 hours, resulting in a cake-like material. This cake-like material is transferred to a washing tank, where deionized water is added for repeated washing. The washing temperature is controlled at 60-70°C, and washing continues until the pH of the filtrate reaches 7-9, thus removing impurities. Maintaining the final pH within the range of 7-9 removes unreacted magnesium hydroxide and byproducts from the reaction system, ensuring the final product has a slightly alkaline to neutral pH, meeting the safety requirements for cosmetic raw materials. Controlling the washing temperature at 60-70°C increases the solubility of impurities, accelerates washing efficiency, and prevents the hydrolysis of the formed magnesium fatty acid salt coating layer due to excessively high temperatures.

[0030] The process then proceeds to step S6, heat treatment. The cake-like material washed in step S5 is placed in a heat treatment furnace and heated to 100°C at a programmed heating rate of 3°C / min. It is then held at 100°C for 6 hours to complete the heat stabilization treatment, ensuring a stable chemical bond between the magnesium fatty acid salt coating layer and the mica substrate. During heat treatment, excessively rapid heating can cause thermal stress and cracking in the coating layer, while insufficient holding time will prevent complete curing of the magnesium fatty acid salt coating layer, affecting its bonding strength with the mica substrate. After heat treatment, the bond between the magnesium fatty acid salt coating layer and the mica is stronger, resulting in more stable product performance.

[0031] After heat treatment, the process proceeds to step S7, the ultrafine pulverization stage. The cake-shaped material from step S6, after heat treatment, is processed using an ultrafine pulverization process. The speed of the ultrafine pulverizer is set to 8000 to 12000 rpm, and the pulverization time is 15 to 30 minutes. After pulverization, the material is passed through a 200-mesh sieve to obtain the finished product: a composite-modified matte synthetic fluorophlogopite. The ultrafine pulverization process is the key step in achieving the matte effect of this invention. Through high-speed mechanical impact and shearing, the large sheet-like structure of the mica is destroyed, causing microscopic roughening of the mica surface and forming an irregular geometric morphology. This roughened surface can effectively scatter incident light, significantly reducing surface gloss and achieving a matte finish. The parameter control of the ultrafine pulverization process is particularly critical. When the speed is below 8000 rpm, the sheet-like structure of the mica cannot be effectively destroyed, and the matte effect is not obvious; when the speed is above 12000 rpm, the powder becomes too fine, affecting its dispersion performance and skin feel in makeup formulations.

[0032] To verify the technical effects of the present invention, a specific embodiment is provided below for detailed description.

[0033] Example: 1000 g of synthetic fluorophlogopite with a particle size range of 20 to 60 μm was processed according to the above-described process steps. Specific parameters are as follows: In step S1, the synthetic fluorophlogopite was added to deionized water to prepare a slurry with a solid content of 50%, and the temperature was controlled at 70°C while stirring at 300 rpm for 10 minutes. In step S2, 15 g of myristic acid was added as a fatty acid treatment agent, and the temperature was maintained at 70°C while stirring for another 20 minutes. In step S3, magnesium hydroxide was ultrasonically dispersed to prepare a 10% suspension, and the pH was adjusted to 9.5 with ammonia water while stirring at 180 rpm for 10 minutes. In step S4, 15 g of the magnesium hydroxide suspension was added, and the temperature was maintained at 70°C while stirring at 300 rpm for 30 minutes, then the temperature was increased to 90°C at a rate of 2°C / min and held for 10 hours. In step S5, the mixture was vacuum dried at 90°C for 5 hours, and the washing temperature was 65°C until the pH of the filtrate reached 8.5. In step S6, the temperature is increased to 100℃ at a rate of 3℃ / min and held for 6 hours. In step S7, the ultrafine pulverizer is used to pulverize the material at 10000 rpm for 20 minutes, and then the pulverized material is passed through a 200-mesh sieve.

[0034] Performance tests were conducted on the resulting product, and the results are as follows: Gloss testing showed that the gloss of untreated synthetic fluorophlogopite was 45 GU, while the gloss of mica treated with the process of this invention decreased to 4.2 GU, significantly lower than the 12 GU of the stearic acid single coating process and the 18 GU of the silane coupling agent physical adhesion process in the prior art, demonstrating excellent matte finish. Adhesion testing showed that after 500 high-speed stirring simulation tests, the coating layer retention rate of the treated mica still reached 96%, while the coating layer retention rate of mica treated with the stearic acid single coating process was only 62% under the same test conditions, indicating that the fatty acid magnesium salt coating layer generated in situ by this invention has a significant adhesion advantage. Dispersion stability testing showed that when the treated mica was added to the lipstick formula and stored at 60℃ for 30 days, no flocculation or precipitation occurred, indicating that the dispersion stability was more than 3 times higher than that of the prior art. Skin feel evaluation showed that, according to professional evaluators, the powder compact containing mica treated according to this invention showed a 42% improvement in skin adherence and smoothness scores, significantly superior to the heavy feel of mica modified with silane coupling agents. Coating thickness testing, observed under a transmission electron microscope, revealed a fatty acid magnesium salt coating thickness of approximately 80 nm, exhibiting a light and thin texture and excellent oil compatibility.

[0035] As can be clearly seen from the data in the above embodiments, the present invention directly forms a magnesium salt coating layer of fatty acids on the surface of mica through a wet in-situ generation process, effectively solving the technical problems of weak adhesion and easy peeling of the coating layer in the prior art. Simultaneously, the ultra-fine grinding process creates microscopic roughness on the mica surface, significantly reducing surface gloss and achieving an excellent matte finish. The in-situ generated coating layer is uniform and dense, effectively solving the agglomeration problem caused by direct mixing of purchased powders and significantly improving the dispersion stability of modified mica in organic systems. The magnesium salt coating layer is thin and lightweight, avoiding the heaviness and stickiness caused by silane coupling agent modification, giving the mica powder excellent skin-like adhesion and a smooth feel.

[0036] In the above specific embodiments, the selection of each process parameter has been optimized in detail. Regarding the temperature parameter, a reaction temperature range of 60 to 80°C ensures both sufficient dissolution and reactivity of the fatty acid treatment agent while avoiding side reactions caused by excessively high temperatures. Regarding the stirring speed parameter, a stirring speed of 200 to 400 rpm in step S1 ensures sufficient dispersion of the mica powder without generating excessive bubbles; a stirring speed of 250 to 350 rpm in step S4 ensures thorough mixing of the reaction system while avoiding excessive bubble generation that could affect the reaction process. Regarding the pH parameter, adjusting the pH to 9 to 10 in step S3 provides the necessary alkaline environment for the saponification reaction, and controlling the pH at the washing endpoint at 7 to 9 ensures that the final product meets the safety requirements for cosmetic raw materials. Regarding the heat treatment parameter, a heating rate of 3°C / min avoids thermal stress cracking of the coating layer due to excessively rapid heating, and holding at 100°C for 6 hours ensures that the coating layer is fully cured and forms a stable chemical bond. Regarding the selection of ultrafine grinding parameters, a rotation speed range of 8000 to 12000 rpm ensures that the mica flake structure can be effectively broken to form a rough surface, while avoiding excessively high rotation speeds that would cause the powder to be too fine and affect the dispersion performance.

[0037] The process method of this invention also has significant environmental and cost advantages. The entire process is a wet process, eliminating dust pollution and meeting the environmental requirements for cosmetic production. The process flow is simple and controllable, the reaction conditions are mild, and it is easy to scale up for industrial production. Compared with existing technologies, the production cost of this invention is reduced by more than 20%, demonstrating excellent economic efficiency.

[0038] In the specific implementation process, the following technical points should be noted. First, regarding raw material selection, synthetic fluorophlogopite that meets cosmetic-grade safety standards should be used to ensure that heavy metal residues comply with regulations. The integrity and whiteness of the mica's flaky structure are key factors affecting the performance of the final product; high-quality mica raw materials with a whiteness of not less than 95% and a silica content of ≤0.1% should be selected. Second, regarding the selection of treatment agents, the choice of fatty acid or amino acid-based treatment agents should be adjusted according to the skin feel requirements of the final product. Magnesium salts formed from myristic acid have good slipperiness and dispersibility, making them a preferred option in this invention; magnesium salts formed from lauric acid have a more refreshing skin feel and are suitable for refreshing makeup products; magnesium salts formed from palmitic acid and stearic acid have stronger coverage and are suitable for concealing products. Third, regarding reaction process control, temperature and time control during the in-situ reaction stage are crucial to the quality of the coating layer formation. Insufficient heat preservation time will lead to incomplete reaction and uneven coating layer coverage; excessive heat preservation time may cause excessive etching of mica, affecting product performance. Finally, regarding post-processing, washing and heat treatment steps have a significant impact on the performance stability of the final product. Insufficient washing can lead to residual alkaline substances affecting the product's pH value and stability; inadequate heat treatment can result in insufficient bonding between the coating layer and the mica substrate, affecting the product's durability.

[0039] In summary, the in-situ matte surface treatment process for synthetic fluorinated phlogopite of the present invention forms a fatty acid magnesium salt coating layer on the mica surface through a wet in-situ generation method, combined with ultra-fine grinding surface roughening treatment, achieving excellent matte effect, significantly improved adhesion, good dispersion stability, and a light skin feel. At the same time, it has the advantages of being environmentally friendly and efficient, and easy to industrialize, and can well meet the performance requirements of high-end color cosmetic products for matte mica powder.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A surface treatment process using a single-agent in-situ generation method to reduce the gloss of synthetic mica and increase its skin-friendly smoothness, characterized in that... Includes the following steps: S1, Slurry preparation: Add synthetic fluorophlogopite to deionized water, slurry until the solid content is 50%, control the temperature at 60-80℃, and stir at 200-400 rpm for 10 minutes. S2, Addition of organic acid treatment agent: Add 0-5% of the mass of synthetic fluorophlogopite as a fatty acid or amino acid treatment agent to the slurry obtained in step S1, and continue stirring at a temperature of 60-80℃ for 20 minutes. S3, Preparation of magnesium hydroxide suspension: Dissolve magnesium hydroxide in deionized water, ultrasonically disperse for 30 minutes to prepare a 10% suspension, adjust the pH to 9-10 using an alkaline regulator, and stir at 150-200 rpm for 10 minutes. S4, In-situ reaction: Add 0-5% of the magnesium hydroxide suspension prepared in step S3 to the slurry of synthesized fluorophlogopite, maintain the temperature at 60-80℃ and stir at 250-350 rpm for 30 minutes, then increase the temperature to 90℃ at a programmed heating rate of 2℃ / min and keep the reaction at 90℃ for 10 hours. S5, Drying and Washing: The material after the reaction in step S4 is dried in a vacuum drying oven at a temperature of 80-100℃ for 4-6 hours to obtain a cake-like material. The cake-like material is then transferred to a washing tank and washed repeatedly with deionized water at a temperature of 60-70℃ until the pH of the filtrate is 7-9. S6, Heat treatment: Place the cake-shaped material washed in step S5 into a heat treatment furnace, heat it to 100°C at a heating rate of 3°C / min, and keep it at 100°C for 6 hours. S7, Ultrafine Grinding: The cake-shaped material after heat treatment in step S6 is processed by ultrafine grinding. The speed of the ultrafine grinder is set to 8000-12000 rpm, the grinding time is 15-30 minutes, and the material is passed through a 200-mesh sieve after grinding.

2. The in-situ matte surface treatment process for synthesized fluorinated phlogopite as described in claim 1, characterized in that, The particle size range of the synthesized fluorophlogopite in step S1 is 10-100 μm.

3. The in-situ matte surface treatment process for synthesized fluorinated phlogopite as described in claim 2, characterized in that, The particle size range of the synthesized fluorophlogopite in step S1 is 20-60 μm, its whiteness is not less than 95%, and its silica content is ≤0.1%.

4. The in-situ matte surface treatment process for synthesized fluorinated phlogopite as described in claim 1, characterized in that, The fatty acid or amino acid treatment agent mentioned in step S2 is selected from one or more of myristic acid, lauric acid, palmitic acid, stearic acid and amino acid derivatives, and the amount of treatment agent added is 1-3% of the mass of the synthesized fluorophlogopite.

5. The in-situ matte surface treatment process for synthesized fluorinated phlogopite as described in claim 1, characterized in that, The ultrasonic dispersion in step S3 uses an ultrasonic cleaner with a frequency of 20-40kHz.

6. The in-situ matte surface treatment process for synthesized fluorinated phlogopite as described in claim 1, characterized in that, In step S4, during the in-situ reaction, fatty acid or amino acid treatment agents undergo a saponification reaction with magnesium hydroxide, generating a magnesium salt coating layer of fatty acid on the mica surface in situ. This coating layer forms a chemical bond with the mica substrate.